Análise metabolômica aplicada a dois genótipos de pinhão-manso (Jatropha curcas L.) com níveis contrastantes de ésteres de forbol - Mélo Neto, Domingos Ferreira de (2023)
The physic nut (Jatropha curcas L.) has been studied mainly for its potential to provide oil for biodiesel production. In addition, the seed cake obtained after extracting the oil contains remarkable nutritional value. However, the toxicity of most jatropha genotypes, attributed to phorbol esters (PE), precludes its use in animal feed. Thus, given the gap of knowledge about EF biosynthesis, this work comparatively evaluated the EF deposition pattern and the metabolome of different tissues and developmental stages of two jatropha genotypes contrasting in PE accumulation, called HPE and LPE. Initially, it was observed that the HPE genotype accumulates PE in the kernel of mature seeds at a concentration of 0.55 µg.mg-1, while PE were not detected in the LPE genotype. In seeds produced by reciprocal grafts of the HPE and LPE genotypes, no effect of grafting on PE accumulation was observed. During fruit development, PE were detected and quantified in all tissues (pericarp, testa, tegmen and endosperm) and developmental stages analyzed (S1, S2, S3, S4 and S5). Distinct PE deposition patterns between maternal and filial tissues were observed. Furthermore, PE were also detected in leaves and roots of the HPE genotype. The detection of PE in the testa isolated and in the roots, are reported in an unprecedented way in the literature. By the non-target metabolomics approach, the roots emerged as the main repository of terpenoids, especially sesqui and diterpenoids in both genotypes. However, for most of the annotated diterpenoids, higher relative concentrations were seen in the HPE genotype, among them, diterpenoids with tigliane skeleton, the one found in the PE, while the LPE genotype showed higher relative concentrations of sesquiterpenoids. Also in the roots, higher concentrations of neolignans were observed in the LPE genotype, while the HPE genotype tends to accumulate more lignans. During pericarp and testa development, mainly differences in the deposition pattern of phenolic compounds such as flavonoids, chlorogenic acids and hydrolysable tannins were seen. Already in tegmen, there was a sharp drop in the concentration of membrane lipids, accompanied by an increase in several oxylipins. In conclusion, this work detailed the distribution of EF in J. curcas, and explored a rich-set of metabolomic data based on hyphenated liquid chromatography and high-resolution mass spectrometry that may contribute to the understanding of EF biosynthesis, in addition to having been demonstrated differences in the distribution of metabolites of other chemical classes among genotypes, tissues and developmental stages.